La connaissance de soi - Valdivia Fuenzalida, José Antonio (Revue des sciences philosophiques et théologiques, 2016)
This work offers a detailed analysis of Peter of John Olivi’s argument used in article 19 of his Impugnatio quorundam articulorum Arnaldi Galliardi (1282) against a position defended by Thomas Aquinas regarding the knowledge that the soul has of itself. Olivi’s text seeks to prove that human beings can know directly the immaterial realities, among which the soul is included. The aim of this analysis is two-fold. On the one hand, it intends to bring out a problem generated by Aquinas’ theory surrounding the knowledge that the soul has of itself, at least according to the way in which such a theory appears in the available texts. On the other hand, it seeks to compare the argument and Olivi’s position with the interpretation developed by certain Thomists of Aquinas’ theory. Such a comparison reveals a resemblance that gives rise to a critical examination of these interpretations.